Infovis na Pandemia - Filgueiras, Lucia Vilela Leite; Velloso, Leandro Manuel dos Reis; Jarske, Johne Marcus; Souza, Luiz Sérgio de (Computação Brasil, 2020)
O artigo discute o suporte da ferramenta Infovis na visualização de informações durante a pandemia da Covid-19.